The Development of M-Learning Based on Integration-Interconnection of The Accounting Cycle of Trading Company - Kamadita, Putri Adisti; Laily, Nujmatul (Universitas Negeri Malang, 2018)
This study aims to produce a mobile learning application based on the topic of integration-interconnectionofthe trading company. The application is useful as an alternative to independent learning that can support the learning of accounting students .This research was a development research which refers to the development procedure of Borg and Gall which was modified into seven steps. Data in this study were collected using a questionnaire. The results of the study showed that the percentage of eligibility of the material expert validator was 73%, the media expert validator was 98%, the integration-interconnection expert validator was 75%, and the respondent was 79%. The average percentage of eligibility is 81 %. This number means that the application is very feasible to use. Some suggestions that can be given for further development of the application are by making indicators of specific expert validation measurements with supporting references; provide competency updates to the application and add new practice questions; the presentation of the verses of the Qur'an and Hadith can be added so that the students' knowledge of the relationship between the Qur'an, Hadith,and accounting becomes wider; as well as product testing, so that the level of effectiveness of learning media products can be known.